PENURUNAN SUHU TUBUH BAYI PADA KEJADIAN IKUTAN PASKA IMUNISASI (KIPI) PENTABIO DENGAN KOMPRES BAWANG MERAH DI PMB HJ. F KOTABARU - Kusvitasari, Hairiana; Reni Pebriani; Lisda Handayani (LPPM Universitas Sari Mulia, 2023)
Background: Fever which often occurs due to the effects of post-immunization side effects (AEFI) is a disorder that often occurs in infants and toddlers. Fever can have negative impacts that can harm the baby, such as dehydration, lack of oxygen, neurological damage and febrile convulsions. in South Kalimantan, based on the KIPI Regional Committee (Komda) report, in 2020 KIPI DPT-HB accounted for 74% of cases, in 2021 there were 71% of cases and in the January-July 2022 period there were 67% of cases. AEFI cases that occur include fever (38%). One of the non-pharmacological therapies to reduce temperature is red onions (Allium cepa variety ascalonicum). Objective: To determine the decrease in body temperature during secondary events after Pentabio immunization (AEFI) with shallot compress at PMB HJ.F Kotabaru. Method: The research method used is a quantitative descriptive study. The population in this study were babies and 30 people underwent pentabio immunization in November 2022 at PMB Hj. F. The sample used an accidental sampling technique, namely 12 babies who had been given pentabio immunization in January 2023 at PMB Hj. F Kotabaru. Data were collected using observation sheets which were analyzed in the form of a frequency distribution. Results: The results of the study showed that of the 12 respondents, 10 babies (83.3%) experienced a fever after pentabio immunization, their fever decreased after being given a red onion compress. Conclusion: Onion compress is proven to have properties that can reduce the baby's body temperature due to AEFI pentabio. This is an alternative that can be done to reduce fever after pentabio immunization without using chemical-based drugs Keywords: Infant Body Temperature, Red Onion, AEFI (Adverse Events Following Immunization)